Vagal tone: effects on sensitivity, motility, and inflammation. Issue 4 (24th March 2016) - Bonaz, B.; Sinniger, V.; Pellissier, S.
Abstract: The vagus nerve (VN) is a key element of the autonomic nervous system. As a mixed nerve, the VN contributes to the bidirectional interactions between the brain and the gut, i.e., the brain‐gut axis. In particular, after integration in the central autonomic network of peripheral sensations such as inflammation and pain via vagal and spinal afferents, an efferent response through modulation of preganglionic parasympathetic neurons of the dorsal motor nucleus of the vagus and/or preganglionic sympathetic neurons of the spinal cord is able to modulate gastrointestinal nociception, motility, and inflammation. A low vagal tone, as assessed by heart rate variability, a marker of the sympatho‐vagal balance, is observed in functional digestive disorders and inflammatory bowel diseases. To restore a normal vagal tone appears as a goal in such diseases. Among the therapeutic tools, such as drugs targeting the cholinergic system and/or complementary medicine (hypnosis, meditation…), deep breathing, physical exercise, VN stimulation (VNS), either invasive or non‐invasive, appears as innovative. There is new evidence in the current issue of this Journal supporting the role of VNS in the modulation of gastrointestinal functions. Abstract : The vagus nerve is involved in the control of gastrointestinal sensitivity, motility, and inflammation. A low vagal tone, as assessed by heart rate variability, is a marker of autonomic dysfunction that might favor dysfunction of the gastrointestinal tract. Restoration of vagal tone is a therapeutic target in some gastrointestinal diseases. Vagus nerve stimulation, either invasive or non‐invasive, opens therapeutic avenues.